2018
DOI: 10.1111/his.13508
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding in pancreatic cancer revisited: validation of the ITBCC scoring system

Abstract: ITBCC scoring is a simple, reliable and reproducible method to evaluate BD in PDAC and facilitates its documentation in histopathology reports, allowing the prognostic stratification of PDAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Tumour budding is a hallmark of cancer invasion and has been recently validated as a promising prognostic marker in colon cancer, oesophageal cancer, pancreatic cancer, lung cancer and oral cancer . Interestingly, the meta‐analyses conducted on the published studies confirm the prognostic value of tumour budding in oesophageal, colorectal and oral cancers .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Tumour budding is a hallmark of cancer invasion and has been recently validated as a promising prognostic marker in colon cancer, oesophageal cancer, pancreatic cancer, lung cancer and oral cancer . Interestingly, the meta‐analyses conducted on the published studies confirm the prognostic value of tumour budding in oesophageal, colorectal and oral cancers .…”
Section: Discussionmentioning
confidence: 94%
“…In oral squamous cell carcinoma, evaluation of tumour budding using cytokeratin produced higher reproducibility than H&E staining, and interobserver variation was higher among less experienced examiners . Indeed, while pan‐cytokeratin staining can detect more tumour budding, H&E staining has been used successfully in several studies with good reliability and reproducibility . Thus, at present routine assessment of tumour budding with H&E staining can be used, while pan‐cytokeratin staining may be considered in selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on colorectal and other gastrointestinal cancers have shown that careful analysis of tumour budding [Tb] and poorly differentiated clusters [PDCs] at the tumour invasion front may substantially improve their prognostic evaluation. [6][7][8][9][10][11][12][13] The aim of this study was to evaluate these histological parameters [Tb and PDCs] on a relatively large series of CrD-SBCs collected through the Small Bowel Cancer Italian Consortium, and hopefully to improve the prognostic characterisation of this poorly known and relatively rare subset of cancers.…”
Section: Introductionmentioning
confidence: 99%